The relationship between structure and specificity in the plant nitrilases - Woodward, Jeremy David (Department of Molecular and Cell Biology, 2015)
Nitrilases (EC 3.5.5.1) catalyse the enantioselective hydrolysis of a variety of organic nitriles to the corresponding amide and/ or carboxylic acid. These reactions are important in the manufacture of fine chemicals, pharmaceutical intermediates, plastics and paints. Industrial uses of nitrilases are limited however, as wild-type enzymes suffer from limitations such as: a lack of control of the acid:amide ratio of products, and limited availability of substrate specificities.